Efficacy and other nutrition evidence for Vitamin A crops - De Moura, Fabiana F. (International Food Policy Research Institute, 2014)
Biofortified crops as sources of vitamin A contain provitamin A carotenoids, which are a precursor of vitamin A, similar to those found in some plant foods like carrots, mangos, and papaya. Two important factors to consider in the provitamin A crops are retention and bioavailability. The bioavailability of the most common plant provitamin A (beta-carotene) varies widely in relation to the food crop, genotype, cooking method, individual genetic factors, and consumption of fat with the meal. Bioconversion of dietary beta-carotene to retinol across plant foods ranges from 3 to 28:1 by weight (1). Food carotenoid degradation displays exponential decay patterns during storage and varies with the food matrix, crop genotype, and form of storage. It increases directly with time and temperature during storage as well as with exposure to high temperature, light, acids, and oxygen during processing. Because the bioconversion of provitamin A carotenoids to vitamin A is homeostatically regulated, excess toxic accumulation of retinol is prevented. Described below are the studies on retention, bioavailability and the efficacy trials conducted to date on biofortified provitamin A crops.